Upaya Meningkatkan Pengembangan Nilai–Nilai Budaya dan Karakter Bangsa Melalui Penerapan Pendekatan PAIKEM pada Mata Pelajaran Keagamaan di MAN Kendal - Asnawi, Muhamad (Nusantara: Jurnal Pendidikan Indonesia, 2021)
The national character building that has been pursued in various forms has not been implemented optimally. Today there are many anarchist acts, social conflicts, bad language and disrespect. All of this reinforces the uncertainty of the identity, culture and character of the nation. The specific purpose of this study was to assess the feasibility of the PAIKEM method in teaching and learning practices in MAN Kendal. While the overall goal is to form a growth model for integrated education that incorporates cultural values ??and national character into teaching and learning practices, especially in the subjects of the Qur'an Hadith, Aqidah Ahklaq, and Fiqh in MAN Kendal. This study uses the school action research method (PTS) with data collection techniques through observation, field data notes, interviews, test results and notes on the results of reflections/discussions conducted by researchers and collaborative friends (research partners). The results of the study show that incorporating the development of cultural values ??and national character into all subjects is not a difficult task, but it is necessary to do it. The research results show that teachers at MAN Kendal develop a better understanding and mastery of PAIKEM, which has an impact on the growth of cultural values ??and national character.